Effect of Freeze-Dried Soyghurt on Malondialdehyde (MDA) Levels in Hypercholesterolemic Rats - Eka Noneng Nawangsih; Aprilia Grace; Bagus Natakusuma Tirtawijaya (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
The reduction of malondialdehyde (MDA) levels, a biomarker of lipid peroxidation holds clinical relevance in assessing oxidative stress associated with hypercholesterolemia. This study investigated the potential of freeze-dried soybean sourdough as a non-pharmacological intervention to lower cholesterol and mitigate oxidative stress in hypercholesterolemic rats. Thirty male Wistar rats were randomly assigned to 5 groups: negative control, positive control, Treatment 1 (high-fat diet containing 30% lard and simvastatin 5 mg/kg body weight), Treatment 2 (high-fat diet supplemented with soybean sourdough at 10 g/kg body weight), and Treatment 3 (high-fat diet combined with soybean sourdough and simvastatin). The intervention period lasted four weeks. Significant reductions in MDA levels were observed in Treatment Groups 1, 2, and 3, with the most pronounced decrease - 45% ( (p < 0.01) - recorded in Treatment Group 2. These findings suggest a possible interaction between soyghurt and simvastatin that may affect simvastatin's efficacy. Further research is needed to further explore this interaction and its underlying mechanisms. Keywords: Hypercholesterolemia, Soyghurt, Simvastatin, Malondialdehyde